Properties of J- Regular modules - Al-Shaibani, Rafid M.; AL-Mothafar, Nuhad S. (Iraqi Journal of Science, 2019)
The present study introduces the concept of J-pure submodules as a generalization of pure submodules. We study some of its basic properties and by using this concept we define the class of J-regular modules, where an R-module M is called J-regular module if every submodule of M is J-pure submodule. Many results about this concept are proved